Draft Genome Sequence of Lactobacillus plantarum BFE 5092 Isolated from Maasai Fermented Milk - Oguntoyinbo, Folarin A. (Genome Announc, 2016)
The draft genome of Lactobacillus plantarum BFE 5092 isolated from the Maasai traditional fermented milk product kule naoto was sequenced, and sequence analysis showed the assembled genome size to be 3,285,094 bp, containing a predicted total of 3,111 protein-encoding genes, 17 rRNAs, and 70 tRNAs.